2002
DOI: 10.1080/09638280110067603
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life after spinal cord injury

Abstract: HRQOL is decreased in the studied population with an SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
88
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(108 citation statements)
references
References 25 publications
13
88
1
6
Order By: Relevance
“…Using the SF-36, studies of persons with SCI in Canada, the United States, Sweden and Australia have indicated significant reductions in HRQOL compared to general populations. [7][8][9][10][11] Most studies report that the greatest difference is seen in Physical Functioning (PF), and scores on Mental Health (MH) and Social Functioning (SF) diverge less from general population scores. 10,11 Older age, unemployment, hospitalization during the last year and various medical complications such as pain, spasticity and incontinence seem to have more negative effects on HRQOL than the level and extent of SCI as such.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the SF-36, studies of persons with SCI in Canada, the United States, Sweden and Australia have indicated significant reductions in HRQOL compared to general populations. [7][8][9][10][11] Most studies report that the greatest difference is seen in Physical Functioning (PF), and scores on Mental Health (MH) and Social Functioning (SF) diverge less from general population scores. 10,11 Older age, unemployment, hospitalization during the last year and various medical complications such as pain, spasticity and incontinence seem to have more negative effects on HRQOL than the level and extent of SCI as such.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Older age, unemployment, hospitalization during the last year and various medical complications such as pain, spasticity and incontinence seem to have more negative effects on HRQOL than the level and extent of SCI as such. 7,9 However, the topic has been relatively little studied in European SCI populations, as well as in persons injured more than 20 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, uma revisão na literatura sobre qualidade de vida e lesão medular, no período de 1990 e 2003, observou que a maioria dos estudos mostrava uma insatisfação com a vida após a lesão, e essa insatisfação estava relacionada principalmente às desvantagens sociais que o indivíduo passava a enfrentar 25 . Já estudo realizado no Canadá, com 587 portadores de lesão medular, membros do Quebec Paraplegic Association, concluiu que idade, emprego e hospitalização são fatores que interferem na inserção social dessa população, assim como em sua qualidade de vida 21 . A exemplo do que ocorreu no presente estudo, pesquisa realizada nos Estados Unidos com pessoas com lesão medular afro-americanas também demonstrou ser a vida sexual, o emprego e os recursos financeiros algumas das facetas mais afetadas na avaliação da qualidade de vida dos entrevistados 26 .…”
Section: Discussionunclassified
“…The 14 independent studies 1, 12,14,15,26,27,[35][36][37][38][39][40][41][42][43][44] included in the meta-analysis provided data for 9868 participants (Table 1). The majority of the data originated from the USA (n ¼ 10 studies), with studies from Australia (n ¼ 2 studies), Canada (n ¼ 1 study) and Norway (n ¼ 1 study) also contributing.…”
Section: Study Characteristicsmentioning
confidence: 99%